Інтерпретативні матриці історичного наративу - Ліщук-Торчинська, Тетяна Петрівна; Lishchuk-Torchynska, Tetiana P. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Досліджено основні теоретичні підходи в аналізі інтерпретації минулого. З’ясовано відмінності в пред-ставлених теоретиками інтерпретативних схемах в аспекті їх застосування до минулого. Визначено основні компоненти інтерпретативних матриць історичного наративу. Постульовано міждисциплінарний підхід щодо розвитку теорії та у сфері практичного застосування інтерпретативних матриць історичного наративу. The basic position in the development of approaches to the analysis of the interpretation of the past from the beginnings of the theoretical foundations of modern historical science – in the teachings of Johann G. Droyzen and Sharles V. Langlois and Sharles Seignobos – to phenomenological-hermenevtic version of the methodology of the humanities in the interpretation of historical narrative are investigated. The differences in the presentation by G. Droyzen, Sharles V. Langlois and Sharles Seignobos, P. Ricoer, J. Guillaume and D. Maldide interpretative schemes in terms of their application of the past are shown. The main components of the interpretative matrix of historical narratives which is the author’s intent, the composition of the narrative, the image of the past as the semantic center, methodology or research paradigm, in whit the author works. An interdisciplinary approach to the development on the theory and the practical application of interpretive matrix of historical narrative is postulated.
Interpretative Matrix of Historical Narrative
Keywords: сутність інтерпретації; the essence interpretation; типи (види) інтерпретації; types/kinds interpretation; смислоутворюючий центр інтерпретації історичного наративу; a semantic interpretation center of historical narrative; феноменолого-герменевтична епістемологія інтерпретації; phenomenological-hermeneutic interpretation of epistemology